Leather goods comfort: an approach to identify its variables and influence - Beltrán Jamaica, Aldemar
Leather goods is an age-old tradition born of man’s need to carry elements with himself, in fact it is considered to have been used in antiquity in activities such as hunting and farming, even hieroglyphics in Egypt exhibit men who possess a kind of bag strapped to the waist; later, in the fourteenth century, these bags were used to carry money for men and to demonstrate social status for women, who carried perfume, lipstick and fan, then with the changes of the nineteenth century and the appearance of transport by train, Its capacity and structure changed, since then it has evolved towards an object of daily use and an indispensable accessory, to the point of finding a great variety of typologies in the market, from the simple and small lady’s purse to party, passing by the leather briefcase for the business executive man to the military’s backpack for the campaign. Leather goods have not been benefited from much research as its main branch, clothing, however, studies have focused mainly on ergonomic advances, internal distribution of elements and loads. These analyzes focused on the applied technology and the aesthetics of these articles, have been led by companies with a long history that destine resources to R+D+I activities, as well as small entrepreneurs generally in the area of design. These studies have emphasized in bags to carry on the back, presenting them the greatest technological development in the market due to the extensive studies of use in school age and in the militia due to the weight capacity that bearers can carry.The study developed here addresses the analysis of bags, handbags and / or briefcases from a global perspective due to the breadth of the development of these products by the fashion industry. Allowing a representative observation of these products and their use through laboratory tests, which involve an application in the field of biomechanics from the postural analysis and in the execution of the human gait. Similarly, an approach to the user’s thinking and experience in relation to comfort in leather goods and what it represents to him / her, given the conditions of a particular everyday context.Given the above, it is meritorious to make a contribution to the sector from the perspective of comfort and what it can represent for the user, academy and industry, providing resources and starting material for future studies that deepen the aspects discussed here; therefore the intention to emphasize in handbags due to the low development and research versus the backpacks.